PEMBERDAYAAN ORANGTUA BERBASIS KEGIATAN PARENTING UNTUK MENANAMKAN KARAKTER AKHLAK MULIA PESERTA DIDIK - Napisah, Cucu (PT. Solusi Komunikasi Terapan, 2023)
Many parents do not understand parenting skills. The aim of this research is to obtain an overview and information about (1) planning for parent empowerment based on parenting activities (2) organizing parent empowerment based on parenting activities (3) Implementation of parent empowerment based on parenting activities (4) evaluation of parent empowerment based on parenting activities (5) obstacles and solutions for empowering parents based on parenting activities. This research uses a qualitative approach and study methods in kindergarten. IPIMAC and TK. Bina Muda Cicalengka District. Bandung. The research results illustrate that (1) in planning, goals have been determined, identified existing problems, identified situations and developed plans (2) In organizing, committees have been formed, infrastructure, time allocation, place of activity implementation, search for reliable resources in parenting, looking for material (3) implementation of parenting activities by holding foundation classes, counseling and parent’s day (4) evaluation carried out after the activity is completed to determine the level of success of the activity (5) obstacles and solutions that occur in parenting activities to achieve the goals that have been set plans must be resolved immediately by finding a solution and implementing the solution. The general conclusion from this research is that parental empowerment based on parenting activities that have been carried out with the guidance of a psychologist can make a positive contribution to the development of students’ noble moral character. The development of students’ character shows positive changes in both behavior and speech.